The Philosopher's Arete or theStructure of Plato's Parmenides - Gutierrez, Raúl (1999)
The controversy conceming the unity of Plato's Parmenides and the meaning of its first part is stillongoing. The A. proposes a solution, pointing out its structural coincidence with the Republic's simile of the line. This leads him to confine young Socrates in the segment that corresponds to óuivoux and old Parmenides in the vór¡olc; segment. As the one who "possesses insight" of truth based on his apprehension of the One-Good. Parmenides is the actual representative of the philosopher's arete.